Dampak dari Parameter Variasi Koneksi, Node dan Kecepatan Node Terhadap Delay pada Routing Protocol AODV dan BATMAN Jaringan MANET - Dodon Turianto Nugrahadi; M Reza Faisal; Liling Triyasmono; Muhammad Janawi (Jurnal Komputasi, 2020)
Mobile ad-hoc Network (MANET) is a multihop wireless network that a many collection of mobile nodes that are dynamic. MANET each node on the network have the same position, so it needs the appropriate routing protocol, to support the exchange of data to be optimal. In this study, the routing protocol to be tested is AODV and BATMAN based scenario increasing the number of connections, nodes and speed. Simulation parameter scenarios is number connection 1 UDP, 2 UDP, 3 UDP, and number of node 25 node, 50 node, 100 node, and then number node speed 20 m/s, 50 m/s. in this AODV routing protocol will establish a rute from the source node to the destination only if there is a request from the source node. BATMAN routing protocols, all decisions and information disseminated throughout the node and will regularly update on each node. The performance parameters to be measured such as delay by using OMNET ++ 4.6. Output of simulation will analysis with two way anova and multivariate to know correlation between variation scenario impact to delay. The results obtained in this study AODV and BATMAN have their respective advantages, analisys with two-way anova show that both AODV and BATMAN get the impact of the scenario from incrising the number of connections, the number of nodes and the number of nodes speed with a p-value of 0.012212 (<0.05) with two-way anova. From all scenarios, the number of UDP connections has the greatest impact, from UDP 1, UDP 2 and UDP 3. Followed by the number of speed 50 and node 100. So it can be concluded that the connection has an effect on increasing delay. The increasing number of speed and nodes can contribute to an increase in delay if number of nodes above 100 and speed above 50. With multivariate analysis, the BATMAN protocol had the most impact on the delay under the scenario then AODV.